PENERAPAN MODEL ROLE PLAYING TERHADAP SELF EFFICACY BELAJAR SISWA DI SMA NEGERI 1 LEDO - Nur Aslinda; Warneri Warneri; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to find out how the application of role playing models to student self-efficacy on economic subjects in class X IPS at SMA Negeri 1 Ledo. The research method was quasy experimental design with nonequivalent control grup design The Subject of this research is X IPS 1 as controlled class and X IPS 2 as experiment class which the total is 54 students. The technique of data collection were done by direct observation techniques and analayzed by percentage descriptive analysis and descriptive statistical analysis. Based on the results of the research, the percentage of student self-efficacy using role playing learning models in class X IPS at the first meeting amounted to 66.32% sufficient category and at the second meeting 78.06% in the good category. The percentage of  student self-efficacy without using the role playing learning models was the conventional learning model in class X IPS 1 at the first meeting of 50.55% in the less category and at the second meeting 62.09% in the sufficient category.  The value of effect size is  1.13 and inclued in the high catogey. This shows that the application of role playing learning models was more effective in increasing self-efficacy of student learning on economic subjects than conventional learning models. Keyword: Role Playing, Student Self-Efficacy